Impact of a national external quality assessment scheme for breast pathology in the UK. Issue 2 (27th January 2006) - Ellis, I O; Coleman, D; Wells, C; Kodikara, S; Paish, E M; Moss, S; Al-sam, S; Anderson, N; Bobrow, L; Buley, I; Connolly, C E; Dallimore, N S; et al.
Abstract : Background: This article presents the results and observed effects of the UK National Health Service Breast Screening Programme (NHSBSP) external quality assurance scheme in breast histopathology. Aims/Methods: The major objectives were to monitor and improve the consistency of diagnoses made by pathologists and the quality of prognostic information in pathology reports. The scheme is based on a twice yearly circulation of 12 cases to over 600 registered participants. The level of agreement was generally measured using κ statistics. Results: Four main situations were encountered with respect to diagnostic consistency, namely: (1) where consistency is naturally very high—this included diagnosing in situ and invasive carcinomas (and certain distinctive subtypes) and uncomplicated benign lesions; (2) where the level of consistency was low but could be improved by making guidelines more detailed and explicit—this included histological grading; (3) where consistency could be improved but only by changing the system of classification—this included classification of ductal carcinoma in situ; and (4) where no improvement in consistency could be achieved—this included diagnosing atypical hyperplasia and reporting vascular invasion. Size measurements were more consistent for invasive than in situ carcinomas. Even in cases where there is a high level of agreement on tumour size, a few widely outlying measurements were encountered, for which no explanation is readily forthcoming. Conclusions: These results broadly confirm the robustness of the systems of breast disease diagnosis and classification adopted by the NHSBSP, and also identify areas where improvement or new approaches are required.